Germline Mutational Landscape in Chinese Patients With Advanced Breast Cancer - Zhang, Jiayang; Wang, Nan; Zheng, Tiantian; Lu, Tan; Zhang, Ruyan; Ran, Ran; Li, Kun; Huang, Yong; Xie, Feng; Zhang, Yue; Jia, Shidong; Yu, Jianjun; et al. (Frontiers in Oncology, 2022)
Background Genetic testing for breast cancer (BC) patients may shift the paradigm towards more personalized management and treatment strategies. While gene alterations may be ethnic-specific in breast cancer, our understanding of genetic epidemiology of BC remains mainly driven by data from Caucasian populations and further limited to selected handful of genes. Methods We collected whole blood samples from 356 BC patients at metastatic first line BC and primary stage IV disease at Beijing Cancer Hospital between Jan. 2013 to Dec. 2019. A comprehensive 600-gene cancer panel was used to detect germline variants in the covered genes with a median 300x sequencing depth. Variants were classified into pathogenic, likely pathogenic, variant of uncertain significance, likely benign and benign groups according to the ACMG/AMP Standards and Guidelines. Pathogenic and likely pathogenic variants were considered as deleterious mutations. Results The median age of 356 BC patients was 49 years (range, 21-87 years) at the first diagnosis of BC. Deleterious germline mutations across 48 cancer-related genes were identified in 21.6% (77/356) of the patients. The most prevalent mutations were BRCA1/2 mutations (7.0%), followed by ATM and RAD50 mutations (1.4% each). In addition, patients with family history were more likely to carry BRCA1 mutations (P=0.04). Moreover, patients with triple-negative breast cancer (TNBC) were more likely to harbor BRCA1 mutations than those with HR+ or HER2+ breast cancer (P=0.006). While there was no significant survival difference observed in BRCA1/2 carriers relative to non-carriers, patients with DNA damage repair (DDR) gene mutations (mostly frequently BRCA, ATM, RAD50) had worse disease-free survival (P=0.02). Conclusions The most prevalent germline mutations in a large cohort of Chinese patients with advanced BC were BRCA1/2 mutations, followed by ATM and RAD50 mutations. In total, approximately 16.0% (57/356) of patients carry deleterious mutations in DDR pathway. Patients with breast or ovarian cancer family history were more likely to carry BRCA1/2 mutations, and ones with DDR mutations had worse survival. These findings suggest that DDR mutations are prevalent in Chinese BC patients who may potentially benefit from treatment with Poly (ADP-ribose) polymerase inhibitors.